Rights versus Risks: The Tension in Sexual Education for Learners with Intellectual Disability - Bouic, Isabelle (Department of Psychology, 2021)
South African society has a high prevalence of sexual abuse and violence, and those with intellectual disability (ID) are more likely to be victimized. Therefore, there is a need for sexual education programmes that cater to learners with ID. In South Africa, national policy overlooks individuals with moderate to severe intellectual disabilities who are predominately placed in separate special needs schools. Gaps in skills, resources and attitudes required for effective curriculum implementation are reported barriers to implementing sexual education. Furthermore, barriers to implementation are compounded by pre-existing societal stigma surrounding both sexuality and disability. This exploratory study thus aimed to examine educators' experiences of using the Western Cape Forum for Intellectual Disability's All About Me sexual education programme. Interviews conducted with 15 educators and management staff aim to explore, describe and identify the facilitating factors and barriers to its implementation. The research design entails Template Analysis of interview data, using a priori codes drawn from existing literature in the interpretation of results. The key finding was that school staff struggle to balance learners' rights to sexual education while protecting them from sexual risks. Recommendations are made for a whole-school balance of rights versus risks approach, supported by policy, and teaching sexual education from a young age – prior to puberty and maturation. Effective implementation entails a progressive curriculum with accessible resources that are contextually relevant. Addressing attitudes via regular training and open discussions are necessary for a shift in attitudes regarding ID and sexuality, for which parents are to be included in the process. Further research is required into effective sexual education for those with ID